2008
DOI: 10.1038/ncb1742
|View full text |Cite
|
Sign up to set email alerts
|

Genomic stability and tumour suppression by the APC/C cofactor Cdh1

Abstract: The anaphase promoting complex or cyclosome (APC/C) is a ubiquitin protein ligase that, together with Cdc20 or Cdh1, targets cell-cycle proteins for degradation. APC/C-Cdh1 specifically promotes protein degradation in late mitosis and G1. Mutant embryos lacking Cdh1 die at E9.5-E10.5 due to defects in the endoreduplication of trophoblast cells and placental malfunction. This lethality is prevented when Cdh1 is expressed in the placenta. Cdh1-deficient cells proliferate inefficiently and accumulate numeric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
446
0
18

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 340 publications
(501 citation statements)
references
References 45 publications
37
446
0
18
Order By: Relevance
“…With Cdh1 playing such a vital role in mediating the degradation of major cell cycle regulators, it is not surprising that Cdh1 was recently characterized to be a bona fide tumor suppressor [26]. Therefore, understanding how the tumor suppressor function of Cdh1 is regulated becomes increasingly more important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With Cdh1 playing such a vital role in mediating the degradation of major cell cycle regulators, it is not surprising that Cdh1 was recently characterized to be a bona fide tumor suppressor [26]. Therefore, understanding how the tumor suppressor function of Cdh1 is regulated becomes increasingly more important.…”
Section: Discussionmentioning
confidence: 99%
“…Although Cdh1 displays many characteristics of a bona fide tumor suppressor, only recently has this been established. GarciaHiguera et al [26] demonstrated that heterozygous Cdh1 mice (Cdh1 +/− ) develop epithelial tumors, suggesting a haploinsufficient role of Cdh1 in tumor suppression. Moreover, reduced Cdh1 expression was observed in hematological neoplasias and solid tumors [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, tumor suppressor genes (eg, CDH1 and SYK) were transcriptionally activated and highly expressed, whereas the genes regulating cell proliferation (eg, uPAR, FN and EGFR) were significantly reduced in ERp29-transfected MDA-MB-231 cells (Supplementary Table 1, Figure 7). E-cadherin suppressed tumor formation by preventing genomic instability, 42 whereas SYK negatively regulated cell proliferation, invasion and tumor formation. 43 EGFR and uPAR were found to positively regulate cell migration, invasion and tumorigenesis.…”
mentioning
confidence: 99%